On substantiation of mechanism of lateral extrusion of the crust of the Mountain Crimea - V. Gonchar (Геофизический журнал, 2015)
Numerical modeling of the crust deformations in the section of the Southwest Crimea subjected to rear indentor compression from the side of the East-Black Sea depression has been fulfilled taking into account regularities of seismic activity distribution. As a result mechanism of lateral extrusion has been specified, thrust-fault of orogen to the West-Black Sea depression is predicted.